Novel resistor cabinet shell - LU SHUANGJIA; SUN GUOQIANG; LIN XIANPIN (2020)
The invention discloses a novel resistor cabinet shell, which comprises a resistor cabinet base, a resistor cabinet, a protective cover, supporting frames, a solar panel, air inlets and air filteringmechanisms. The resistor cabinet is arranged on the resistor cabinet base. The protective cover is arranged at the top of the resistor cabinet. The paired supporting frames are arranged at the top ofthe protective cover. The solar panel is arranged at the tops of the supporting frames. The symmetrical air inlets are formed in the left side wall and the right side wall of the resistor cabinet. Theair filtering mechanisms are arranged on the air inlets. Compared with the prior art, the novel resistor cabinet shell is simple in structure and reasonable in design, the protection level of the resistor cabinet is improved while autonomous heat dissipation of the resistor cabinet is achieved through solar energy, external dust and water vapor are prevented from entering the resistor cabinet, and the service life of compo